Physical activity and the risk of SARS-CoV-2 infection, severe COVID-19 illness and COVID-19 related mortality in South Korea: a nationwide cohort study - Lee, S. W.; Lee, J.; Moon, S. Y.; Jin, H. Y.; Yang, J. M.; Ogino, S.; Song, M.; Hong, S. H.; Ghayda, R. A.; Kronbichler, A.; Koyanagi, A.; Jacob, L.; et al. (British Journal of Sports Medicine, 2022)
Purpose: To determine the potential associations between physical activity and risk of SARS-CoV-2 infection, severe illness from COVID-19 and COVID-19 related death using a nationwide cohort from South Korea.